PENGARUH GENDER, TEKANAN KETAATAN,PENGETAHUAN, KEAHLIAN, DAN PENGALAMAN TERHADAP KUALITAS AUDIT STUDI PADA INSPEKTORAT PROVINSI DIY - Felia Nawang Wulan; Arif Sapta Yuniarto (Universitas Ahmad Dahlan, 2015)
This study examines the influence of gender, compliance pressure, audit knowledge, expertise, and auditor experience to audit quality. The respondents in this study were auditors who worked in The Inspectorate of DIY. The number of auditor who observed in this study was 40 auditors. They came from some auditors who worked in The Inspectorate of DIY. The method of determining the sample was purposive sampling method, the data processing methods that used by researcher were the multiple regression analysis. The result shows that the gender,compliance pressure, audit knowledge, expertise, and auditor experience simultaneously and significantly to audit quality.